A signal-on fluorescence sensor for hydrogen sulphide detection in environmental samples based on silver-mediated base pairs. Issue 2 (12th December 2019) - Huang, Yanling; Yue, Guiyin; Luo, Fang; Guo, Longhua; Qiu, Bin; Lin, Zhenyu
Abstract : A signal-on fluorescent sensor was developed for the hydrogen sulfide detection in the air near a garbage station based on the silver-mediated base pairs. Abstract : Hydrogen sulfide (H2 S) is a dramatically toxic gas molecule; long term exposure to H2 S environment poses a serious threat to human health. It is highly imperative to develop sensitive and selective methods for H2 S detection. In this study, a signal-on fluorescence biosensor for the H2 S (used to represent the total amount of H2 S, HS − and S 2− ) detection was developed based on silver-mediated base pairs (C–Ag + –C). Two separate C-rich single-stranded DNAs (ssDNAs) were synthesized, namely, one was labeled with fluorescein (6-carboxyfluorescein, FAM) and the other was labeled with quencher (black hole quencher, BHQ1). The two ssDNAs were in a flexible single strand owing to the mismatch of the ssDNA, and hence, significant fluorescence intensity was observed. In the presence of Ag +, DNA probes could selectively capture Ag + to form double stranded DNA (dsDNA) via the C–Ag + –C base pairs, which made the quench of FAM by BHQ1 and low fluorescence signal was detected. With the addition of H2 S to the system, the dsDNA was decomposed into ssDNA since Ag + could be released from C–Ag + –C by the formation of a more stable complex Ag2 S, which resulted in the recovery of the fluorescence intensity. The enhanced fluorescence intensity had a linear relationship with H2 S concentration in the range from 0.5 to 20 μM with a detection limit (LOD) of 0.16 μM (S/N = 3). The proposed system was applied to detect H2 S (used to represent the total amount of H2 S, HS − and S 2− ) in air near a garbage station with satisfying results.